Biodegradable Polymeric Nanoparticles Containing an Immune Checkpoint Inhibitor (aPDL1) to Locally Induce Immune Responses in the Central Nervous System. (9th July 2021) - Zhang, Ming; Jiang, Xuefeng; Zhang, Qicheng; Zheng, Tao; Mohammadniaei, Mohsen; Wang, Wentao; Shen, Jian; Sun, Yi
Abstract: Immunotherapy is an efficient approach to clinical oncology. However, the immune privilege of the central nervous system (CNS) limits the application of immunotherapeutic strategies for brain cancers, especially glioblastoma (GBM). Tumor resistance to immune checkpoint inhibitors is a further challenge in immunotherapies. To overcome the immunological tolerance of brain tumors, a novel multifunctional nanoparticle (NP) for highly efficient synergetic immunotherapy is reported. The NP contains an anti‐PDL1 antibody (aPDL1), upconverting NPs, and the photosensitizer 5‐ALA; the surface of the NP is conjugated with the B1R kinin ligand to facilitate transport across the blood‐tumor‐barrier. Upon irradiation with a 980 nm laser, 5‐ALA is transformed into protoporphyrin IX, generating reactive oxygen species. Photodynamic therapy (PDT) further promotes intratumoral infiltration of cytotoxic T lymphocytes and sensitizes tumors to PDL1 blockade therapy. It is demonstrated that combining PDT and aPDL1 can effectively suppress GBM growth in mouse models. The proposed NPs provide a novel and effective strategy for boosting anti‐GBM photoimmunotherapy. Abstract : The combination of anti‐programmed cell death‐1 ligand 1‐modified nanoparticles with 980 nm laser irradiation‐triggered activation of protoporphyrin IX, induces the generation of reactive oxygen species, which promotes the intratumoral infiltration of cytotoxic T lymphocytes. In addition, activated tumoricidal M1 macrophages and natural killer cells also contribute to tumor cell elimination.